Buya Hamka's Views on Gathering in Al-Azhar Tafsir and Its Relevance to the Alek Bakajang Tradition - Gusti Rafel; Jani Arni; Saifullah Saifullah (Institut Agama Islam Sumatera Barat, 2024)
Silaturrahmi is a command from Allah as stated in the Qur’an. Buya Hamka, in his Tafsir Al-Azhar, explains that silaturrahmi means fostering bonds of compassion among all human beings, as humanity fundamentally originates from a single soul. This concept of silaturrahmi is also implemented by Indonesian society through various traditions, such as the Alek Bakajang tradition. Alek Bakajang is a longstanding tradition passed down through generations to strengthen relationships among all elements of society in Nagari Gunuang Malintang, Pangkalan Koto Baru Subdistrict, Lima Puluh Kota Regency, West Sumatra. In modern times, this tradition is often associated with